Efficacy of a Digital Mental Health Biopsychosocial Transdiagnostic Intervention With or Without Therapist Assistance for Adults With Anxiety and Depression: Adaptive Randomized Controlled Trial - Brooke Andrews; Britt Klein; Huy Van Nguyen; Denise Corboy; Suzanne McLaren; Shaun Watson (JMIR Publications, 2023)
BackgroundDigital mental health (DMH) interventions incorporating elements that adapt to the evolving needs of consumers have the potential to further our understanding of the optimal intensity of therapist assistance and inform stepped-care models. ObjectiveThe primary objective was to compare the efficacy of a transdiagnostic biopsychosocial DMH program, with or without therapist assistance for adults with subthreshold symptoms or a diagnosis of anxiety or depression. MethodsIn a randomized adaptive clinical trial design, all participants had access to the DMH program, with eligibility to have their program augmented with therapist assistance determined by program engagement or symptom severity. Participants who met stepped-care criteria were randomized to have their treatment program augmented with either low-intensity (10 min/week of video chat support for 7 weeks) or high-intensity (50 min/week of video chat support for 7 weeks) therapist assistance. A total of 103 participants (mean age 34.17, SD 10.50 years) were assessed before (week 0), during (weeks 3 and 6), and after the intervention (week 9) and at the 3-month follow-up (week 21). The effects of 3 treatment conditions (DMH program only, DMH program+low-intensity therapist assistance, and DMH program+high-intensity therapist assistance) on changes in the 2 primary outcomes of anxiety (7-item Generalized Anxiety Disorder Scale [GAD-7]) and depression (9-item Patient Health Questionnaire [PHQ-9]) were assessed using the Cohen d, reliable change index, and mixed-effects linear regression analyses. ResultsThere were no substantial differences in the outcome measures among intervention conditions. However, there were significant time effect changes in most outcomes over time. All 3 intervention conditions demonstrated strong and significant treatment effect changes in GAD-7 and PHQ-9 scores, with absolute Cohen d values ranging from 0.82 to 1.79 (all P<.05). The mixed-effects models revealed that, in the Life Flex program-only condition at week 3, mean GAD-7 and PHQ-9 scores significantly decreased from baseline by 3.54 and 4.38 (all P<.001), respectively. At weeks 6, 9, and 21, GAD-7 and PHQ-9 scores significantly decreased from baseline by at least 6 and 7 points (all P<.001), respectively. Nonresponders at week 3 who were stepped up to therapist assistance increased program engagement and treatment response. At the postintervention time point and 3-month follow-up, 67% (44/65) and 69% (34/49) of the participants, respectively, no longer met diagnostic criteria for anxiety or depression. ConclusionsThe findings highlight that early detection of low engagement and non-treatment response presents an opportunity to effectively intervene by incorporating an adaptive design. Although the study findings indicate that therapist assistance was no more effective than the DMH intervention program alone for reducing symptoms of anxiety or depression, the data highlight the potential influence of participant selection bias and participant preferences within stepped-care treatment models. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12620000422921; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=378317&isReview=true International Registered Report Identifier (IRRID)RR2-10.2196/45040